2015
DOI: 10.1097/mib.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas Species

Abstract: Aeromonas caused mostly mild infections but also moderate and severe infections. A. veronii was more prevalent in patients with IBD and was associated with worse clinical outcomes. Aeromonas caused milder infections in patients without IBD. Other risk factors for severe infection were not found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Multiple genera were significantly enriched in the diseases compared to the healthy controls. Most of these genera have been reported as opportunistic pathogens of the human gut [5867]. These disease-enriched genera typically showed higher abundance and higher variance in disease subjects compared to the healthy ones (first and second columns of Additional file 4: figure 2), while all of these genera exhibit low abundance in the dataset used here (third column of Additional file 4: figure 2).…”
Section: Discussionmentioning
confidence: 91%
“…Multiple genera were significantly enriched in the diseases compared to the healthy controls. Most of these genera have been reported as opportunistic pathogens of the human gut [5867]. These disease-enriched genera typically showed higher abundance and higher variance in disease subjects compared to the healthy ones (first and second columns of Additional file 4: figure 2), while all of these genera exhibit low abundance in the dataset used here (third column of Additional file 4: figure 2).…”
Section: Discussionmentioning
confidence: 91%
“…In one of the ileal samples, we identified an unexpected presence of Aeromonas hydrophila and veronii (5%; see Fig. 2); infection with this enteropathogen is associated with a poor clinical outcome in IBD [27]. In another patient, both the stool and ileal samples contained a high fraction (0.4 and 4.2%) of Fusobacterium varium, which is a species associated with and able to induce ulcerative colitis [28].…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] Aeromonas can be a trigger of flare-ups or the development of IBD and cause a more severe infection in IBD patients than in non-IBD patients. [ 8 ] The incidence of C . difficile in IBD has doubled in recent years, increasing significantly in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The role of Aeromonas species in UC is controversial, but recent studies have suggested that it can trigger UC relapse. [ 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%